Esmolol during cardiopulmonary resuscitation reduces neurological injury in a porcine model of cardiac arrest - Laura Ruggeri (Nature Portfolio, 2021)
Abstract Primary vasopressor efficacy of epinephrine during cardiopulmonary resuscitation (CPR) is due to its α-adrenergic effects. However, epinephrine plays β1-adrenergic actions, which increasing myocardial oxygen consumption may lead to refractory ventricular fibrillation (VF) and poor outcome. Effects of a single dose of esmolol in addition to epinephrine during CPR were investigated in a porcine model of VF with an underlying acute myocardial infarction. VF was ischemically induced in 16 pigs and left untreated for 12 min. During CPR, animals were randomized to receive epinephrine (30 µg/kg) with either esmolol (0.5 mg/kg) or saline (control). Pigs were then observed up to 96 h. Coronary perfusion pressure increased during CPR in the esmolol group compared to control (47 ± 21 vs. 24 ± 10 mmHg at min 5, p < 0.05). In both groups, 7 animals were successfully resuscitated and 4 survived up to 96 h. No significant differences were observed between groups in the total number of defibrillations delivered prior to final resuscitation. Brain histology demonstrated reductions in cortical neuronal degeneration/necrosis (score 0.3 ± 0.5 vs. 1.3 ± 0.5, p < 0.05) and hippocampal microglial activation (6 ± 3 vs. 22 ± 4%, p < 0.01) in the esmolol group compared to control. Lower circulating levels of neuron specific enolase were measured in esmolol animals compared to controls (2[1–3] vs. 21[16–52] ng/mL, p < 0.01). In this preclinical model, β1-blockade during CPR did not facilitate VF termination but provided neuroprotection.